HUBUNGAN PAD, BELANJA MODAL DAN KINERJA KEUANGAN PEMERINTAH DAERAH DI NUSA TENGGARA BARAT - Eka Sintala Dewi Anjani; A. Akram; Lilik Handajani (InFestasi, 2015)
Abstract This research aims to assess the relations between Local Own-source Revenue, capital expenditure and financial performance of the Local Government of West Nusa Tenggara Province, using Partial least square analysis. The assessment were undertaken to the local government of West Nusa Tenggara and 10 districts and cities within Nusa Tenggara region using secondary data including annual financial report of West Nusa Tenggara Government from 2009 to 2013.  The results showed that a effect Local Own-source Revenue on Regional Financial Performance as measured by the ratio of Independence. The study also generate Local Own-source Revenue effect on capital expenditure, and  a effect on capital expenditures on financial performance area. Further, the results show that capital expenditure would mediate relation between local own revenue and regional financial performance. The implication of this research is that it can be used as a reference to making decision relating to regional revenue management specifically for management of  local own-source revenue used for capital expenditure that is directly relating to public services.